Laser-Assisted Reduction of Highly Conductive Circuits Based on Copper Nitrate for Flexible Printed Sensors - Bai, Shi; Zhang, Shigang; Zhou, Weiping; Ma, Delong; Ma, Ying; Joshi, Pooran; Hu, Anming (Nano-Micro Letters, 2017)
Stretchable electronic sensing devices are defining the path toward wearable electronics. High-performance flexible strain sensors attached on clothing or human skin are required for potential applications in the entertainment, health monitoring, and medical care sectors. In this work, conducting copper electrodes were fabricated on polydimethylsiloxane as sensitive stretchable microsensors by integrating laser direct writing and transfer printing approaches. The copper electrode was reduced from copper salt using laser writing rather than the general approach of printing with pre-synthesized copper or copper oxide nanoparticles. An electrical resistivity of 96 μΩ cm was achieved on 40-μm-thick Cu electrodes on flexible substrates. The motion sensing functionality successfully demonstrated a high sensitivity and mechanical robustness. This in situ fabrication method leads to a path toward electronic devices on flexible substrates. Highlights: 1 A novel method to fabricate flexible sensors based on conductive copper circuits by laser-assisted reduction is introduced. 2 The copper nitrate hydroxide (Cu(OH)(NO3)) was reduced by ethylene glycol using laser scanning on glass and polyethylene terephthalate. By transferring the copper electrode onto the polydimethylsiloxane, which acted as stretchable substrate, the electrode exhibits high sensitivity, and its resistivity is as low as 90 μΩ cm. 3 This type of device can be used for motion detection and touch sensors to control electrical devices.